Research recast(ed): S3E3 - Bringing young minds to MacEwan through experiences, experiments, and fun with Dr. Emily Milne, Dr. Kaitlyn Towle, and Steven Campbell - Leschyshyn, Brooklyn; Smadis, Natalie; Milne, Emily; Towle, Kaitlyn; Campbell, Steven (My University, 2023)
On today’s episode, we talk to Dr. Emily Milne, Kaitlyn Towle, and Steven Cambell about MacEwanCYU. With the help of MacEwan, students from Ben Calf Robe can learn about what the university has to offer. Their project helps to inspire young minds and invite them to aspire to a secondary education.
Keywords: MacEwanCYU (child and youth university); Ben Calf Robe; education